PELATIHAN STANDARD OPERATING PROCEDURE (SOP) AKUNTANSI BAGI CALON AUDITOR/JUNIOR AKUNTAN DI MATARAM - Hudaya, Robith; Astuti , Widia; Wardiningsih, Reny; Anwar , Adrianda; Sokarina, Ayudia; Ramdani, Hendi (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
Standard Operating Procedures (SOP) are written guidelines that explain the steps or procedures that must be followed in carrying out a task or activity within an organization. SOP aims to create consistency, effectiveness and efficiency in implementing specific tasks or processes. By following SOPs, organizations can increase operational efficiency because tested and validated procedures can reduce wasted time and resources. Based on field observations by interviewing the Head of the Accounting Services Office (KJA), Resty Yusnirmala Dewi, it was discovered that junior accountants and prospective auditors needed more understanding regarding creating Standard Operating Procedures (SOPs) and reading SOPs. Hence, they needed help with an accounting system with solid controls. This understanding is essential in supporting the smooth running of work in the field so that time and costs can be more efficient. Training on Making Accounting Standard Operating Procedures (SOP) for Prospective Auditors/Junior Accountants in Mataram ran smoothly on August 15 2024. Participants gained additional knowledge about Making Standard Operating Procedures (SOP) and the concept of internal solid control to minimize fraud. Prospective Auditors/Junior Accountants must deepen their use of Visio to create SOPs or workflow diagrams. Understanding the tools will produce good images. Apart from that, the ability to create good SOPs and internal controls must continue to be trained. There is a need to update old SOPs due to changes in business and technology policies